Part III: Artwork

(untitled) (Faculty of Education, Queen's University, 2022)
I enjoy the challenge of using scraps from other people’s projects or donated fabric to create something functional and beautiful. In this case I was given someone’s ‘extra’ nine-patch blocks and then created additional nine-patch and hour-glass blocks which are used alternately in rows. Most of my quilts are donated to organizations that provide them to families in need.